Accessible, Dynamic Web Content Using Instagram. - Wilkinson, Jaci (Information Technology & Libraries, 2018)
This is a case study in dynamic content creation using Instagram's Application Program Interface (API). An embedded feed of the Mansfield Library Archives and Special Collections' (ASC) most recent Instagram posts was created for their website's homepage. The process to harness Instagram's API highlighted competing interests: web services' desire to most efficiently manage content, ASC staff's investment in the latest social media trends, and everyone's institutional commitment to accessibility.